(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
During its early structuralist and typological phases, narratology faced a great deal of difficulty relating theory to practice. The study of narrative texts is both an applied science and a theory in its own right. Its critical challenge as applied narratology is ’So what?’ Why do we need all these subcategories to understand texts? Narratology has been criticized for not producing significant readings as a theory, like deconstruction or Lacanian psychoanalysis. The main objective of this paper is to seek to explore the narratological dimensions of literature and compare the Narrative Theories based on structuralist views. To achieve this goal, first a brief history of narratology is offered to provide an opportunity to discuss the structure and the leaders of the narratology movement, and then the entire structuralist discussion of narratology, its concepts, the procedure, and the practitioners is examined. According to the results, structuralist narratology encompasses the opening of a path to the language of a narrative and, therefore, the decoding of the language to act upon its meaning.